Politici privind inovaţia socială în Marea Britanie - Stănescu, Iulian; Matei, Aura (Calitatea Vieții, 2009)
Social innovation is a rather new concept, it does not have a well defined structure and there is no commonly shared approach in this research area. For this reason, it would be useful to explore the meanings associated with social innovation and its uses in the context of Great Britain’s public policies. The British model is also relevant thanks to its long history of structural changes in governance and framing of public policy, thus establishing practices and models/setting up standards for other administrations. The framing of policies regarding innovation in the public sector and social innovation is a recent endeavor. Following policy formulation stages, the institutional network and main public policy documents are analyzed. Fostering social innovation is strongly connected with the general goal of the British Government to stimulate economic and technological innovation as well as to increase the efficiency of the public sector through innovation. In this context, social innovation stands at the centre of the three sectors – public, private and non-profit. Moreover, social innovation is linked with social entrepreneurship. We are also envisaging a presentation of what the British public sector exemplifies as social innovation, like the Open University and Sure Start. In the recent years, there have also been initiated a series of program aimed at stimulating social innovation. Their structure, financing, applicants and objectives are featured.